2005
DOI: 10.1021/bi050941u
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aromatic Ester fromPiper longumand Its Analogues Inhibit Expression of Cell Adhesion Molecules on Endothelial Cells

Abstract: We report here the isolation and characterization of two active principles, ethyl 3',4',5'-trimethoxycinnamate (1) and piperine (2), from the combined hexane and chloroform extracts of Piper longum. Using primary human umbilical vein endothelial cells, we evaluated the activities of compound 1 on TNF-alpha-induced expression of cell adhesion molecules, viz., ICAM-1, VCAM-1, and E-selectin, which play key roles in controlling various inflammatory diseases. Both compounds 1 and 2 inhibited the TNF-alpha-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 35 publications
0
71
0
6
Order By: Relevance
“…Unlike the situation of nitro group, the introduction of a hydroxyl, methoxyl or acetoxyl to any site on the benzene ring (7-15) led to reduce the activity. Meanwhile, the activities of methoxyl-substituted compounds (18)(19)(20) reduced with increasing the number of substituted methoxy groups. In addition, the presence of methylenedioxy, bromo or chloro groups at some sites also led to reduction of the activity, such as 21-25.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the situation of nitro group, the introduction of a hydroxyl, methoxyl or acetoxyl to any site on the benzene ring (7-15) led to reduce the activity. Meanwhile, the activities of methoxyl-substituted compounds (18)(19)(20) reduced with increasing the number of substituted methoxy groups. In addition, the presence of methylenedioxy, bromo or chloro groups at some sites also led to reduction of the activity, such as 21-25.…”
Section: Resultsmentioning
confidence: 99%
“…10) Due to their common occurrence in plants and their low toxicity, 11,12) cinnamic acid derivatives have attracted much attention of many pharmacologists. In the past decades, cinnamic acid derivatives including natural, semi-synthetic and synthetic compounds had been proven to have a variety of pharmacological activities, 13) such as anticancer, 14,15) antimicrobial, [16][17][18] antioxidative, 18) anti-inflammatory, 15,[19][20][21] anti-Mycobactrium tuberculosis, [22][23][24] antiviral, 25) anti-human immunodeficiency virus (HIV), [26][27][28] antidiabetic, 29) anticholesterolemic, 30) analgesic, 31) hepatoprotective, 32,33) immunoprotective, 34) inducing neural progenitor cell proliferation 35) and anxiolytic activity. 36) Especially, what interests us is that cinnamic acid derivatives also have significant antiparasitic activities on plasmodia, 37) Leishmania 38) and nematode.…”
mentioning
confidence: 99%
“…35,36) The efficacy of several identified compounds have also been tested using in vivo models. [37][38][39] Inhibition of these molecules by various small molecules has been shown to downregulate the expression of cell adhesion molecules and is effective in controlling various inflammatory diseases. 40) This study, confirmed that TNF-a induced NF-kB-DNA complex formation was attenuated in the presence of CA.…”
Section: Discussionmentioning
confidence: 99%
“…Primary endothelial cells were isolated from human umbilical cord using mild trypsinization as described earlier 36 .…”
Section: Cell Culture Experimentsmentioning
confidence: 99%
“…A promising approach for the therapeutic intervention of inflammatory disorders is by pharmacological inhibition of the CAM expression of endothelial cells 33 . In order to develop safer and potent anti-inflammatory agents/drugs, our laboratories have identified a number of small molecules from natural/synthetic sources that efficiently block nuclear accumulation of NF-kB and abrogate TNF-a-induced expression of E-selectin, VCAM-1 and ICAM-1 on human umbilical vein endothelial cells (HUVEC's) [34][35][36] .…”
Section: Introductionmentioning
confidence: 99%